Tumour necrosis factor (TNF)-α-308 gene polymorphism in Indian patients with Takayasu's arteritis - a pilot study - Sandhya, P; Danda, Sumita; Danda, Debashish; Lonarkar, Shraddha; Luke, Shana S; Sinha, Shanta; Joseph, George (Indian journal of medical research (New Delhi, India : 1994), 2013)
Tumour necrosis factor-alpha (TNF-α)- 308 promoter gene polymorphism has been shown to be associated with several autoimmune disorders and infections such as tuberculosis. There is no study on TNF-α gene polymorphism in Takayasu's arteritis (TA) till date. We aimed to study this polymorphism in TA, a granulomatous vasculitis, probably triggered by Mycobacterium tuberculosis. TNF-α - 308 gene polymorphism was studied in 34 patients with TA and 39 healthy controls recruited from Christian Medical College, India. PCR was done followed by enzyme digestion. G and A polymorphisms were analysed. Occurrence of alleles in the disease group was compared with controls as well as with historical controls. GG allele was most frequent in TA and in controls. GA allele was detected in four controls but only in one patient who was the oldest in the study group. AA polymorphism was detected in one control but not in TA. When compared with controls from other populations, it was found that our allelic frequency was similar to that in Japan as well as from USA with mixed population. However, predominantly Caucasian population studied from Netherlands, Germany and England, where TA is rare, had a higher frequency of A allele as compared to our controls. Our preliminary results indicated that G allele at TNF-α - 308 was more common in TA patients and controls similar to that in other Indian as well as Japanese population. Compared to the western population, A allele was relatively less common in our study subjects.